Fire the depths - Lerangis, Peter (Max Tilt, 2017)
Thirteen-year-old Max Tilt discovers an unpublished manuscript by Jules Verne and sets out to find the treasure it describes. But Max and his friend Alex aren't the only ones who know about the treasure...